Quantitative assessment of the dynamics of socioeconomic processes - Romualdas Ginevičius; Martin Schieg; Magdalena Kot-Radojewska; Marta Jarocka (Amfiteatru Economic Journal, 2021)
The efficiency of correlation-regression analysis would significantly expand if both of its essential variables - a dependent and an independent - conveyed the information on the dynamic rather than static state of a phenomenon under consideration. For this objective, the dynamic development of the socioeconomic processes should be based on the quantitative assessment. Existing methodologies call for improvement as they do not fully reflect the state of particular phenomena. In this article, authors provide the quantitative assessment methodology to analyse the dynamics of socioeconomic processes. It was applied for assessing real situations, which confirmed adequacy and applicability of this methodology.
Keywords: C13; C61; B16; 330; socioeconomic processes; their fluctuations; quantitative assessment of the fluctuation dynamics